POLA ASUH ORANGTUA ASUH DI PANTI ASUHAN ANAK AL- HIDAYAH KELURAHAN LABUH BARU BARAT KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Kevin Saraswati; Wilson Wilson; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:The purpose of this study was to find out how good upbringing in the Al-Hidayah Children's Orphanage Labuh Baru Barat Village, Payung Sekaki District, Pekanbaru City, this study used a descriptive method with a quantitative approach. The sample in this study was 20 for questionnaire tests and 30 people for research questionnaires with saturated sampling techniques in which all populations were sampled. The technique to collect data using a questionnaire. Techniques for data analysis using the percentage formula. The results of this study indicate that authoritarian parenting is reasonably good, tolerant parenting is classified as poor and democratic parenting is fairly good. So the three indicators of parenthood, if combined, are pretty good interpretations.Key Words: Parenthood, Foster Parents.